2018
DOI: 10.1111/lcrp.12143
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the decision component of the Activation‐Decision‐Construction‐Action Theory for different reasons to deceive

Abstract: Objectives To explore how reasons to lie impact upon the decision component of Activation‐Decision‐Construction‐Action Theory. Design Specifically, the study looked at how beneficiary of the lie (self vs. another) and additional cost of lying (no cost vs. cost to self/other) might influence decisions to lie. Methods Ninety‐one undergraduate students read four hypothetical scenarios representing the four reasons to lie. They stated whether they would decide to tell the truth/lie for each scenario and also estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In order to behave prosocially and intervene for the benefit of the third party, the child needs to deceive a transgressor who intends to harm his potential victim. It was suggested that in case of other-oriented lies, an increase of the EV of truth-telling and a decrease of the EV of lying might lead to less motivation to lie (Cassidy, 2019). It was of interest for us to examine whether additional positive external gains to the self might encourage children to deceive interventionally.…”
Section: The Role Of Expected Values Of Lie-and Truth-telling In Inte...mentioning
confidence: 99%
“…In order to behave prosocially and intervene for the benefit of the third party, the child needs to deceive a transgressor who intends to harm his potential victim. It was suggested that in case of other-oriented lies, an increase of the EV of truth-telling and a decrease of the EV of lying might lead to less motivation to lie (Cassidy, 2019). It was of interest for us to examine whether additional positive external gains to the self might encourage children to deceive interventionally.…”
Section: The Role Of Expected Values Of Lie-and Truth-telling In Inte...mentioning
confidence: 99%
“…Much of the research on morality and ethical judgments has used the scenario-based approach ( McMahon & Harvey, 2007 ). These scenarios have also been used to study organizational factors associated with dishonest employee behavior in the retail sector ( Jaakson et al, 2017 ), as well as in other research, for example, to find out what motivates consumers to lie ( Argo et al, 2006 ), a person’s reasons for deception ( Cassidy et al, 2019 ), or why students plagiarize or engage in other forms of cheating ( Waltzer & Dahl, 2021 ). Thus, to measure dishonest behavior, researchers often use scenarios because they can accurately reflect individuals’ emotions, intentions, and behaviors in different situations ( Wenzel & Reinhard, 2020 ).…”
Section: The Use Of Hypothetical Scenarios In Research On Dishonestymentioning
confidence: 99%
“…The latter should generate the idea that the interviewer will be able to check what is being said, leading to less verifiable statements from liars. In addition, increasing the perception of the lie verifiability should increase the cognitive load of the liars, which is helpful for lie detection (Cassidy et al, 2018; and discouraging people from lying.…”
Section: Limitations and Guidelines For Further Studiesmentioning
confidence: 99%